2015
DOI: 10.1016/j.anl.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three-dimensional endoscopy in endonasal surgery

Abstract: The 3D endoscope contributes to a more precise anatomical understanding of the posterior structures of the sinuses and skull base and ensures a more precise operation of the instruments. Thus, 3D endoscopes will likely become a standard device for endonasal surgery in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 12 publications
1
42
0
Order By: Relevance
“…The main concern is the loss of stereoscopic vision . With appropriate visualization vital for tissue and anatomical identification, previous research has highlighted the subjective preference for 3D endoscopy, as can be confirmed by our study, with the strength of preference statistically significant ( P = < .001) . 3D endoscopy has shown comfort when opening the dura, improved visualization of complex airway anatomy with higher rates of precision when removing tissue, and increased sinus anatomy understanding in cadaveric dissection.…”
Section: Discussionsupporting
confidence: 79%
“…The main concern is the loss of stereoscopic vision . With appropriate visualization vital for tissue and anatomical identification, previous research has highlighted the subjective preference for 3D endoscopy, as can be confirmed by our study, with the strength of preference statistically significant ( P = < .001) . 3D endoscopy has shown comfort when opening the dura, improved visualization of complex airway anatomy with higher rates of precision when removing tissue, and increased sinus anatomy understanding in cadaveric dissection.…”
Section: Discussionsupporting
confidence: 79%
“…With regard to surgeon fatigue, our experience was in accordance with other reports showing no difference in the degree of fatigue experienced by the chief surgeon and the surgical team between the use of the 2D and 3D systems, except during the early phase of the approach. Studies also showed that the 3D endoscopy may be beneficial in the education of medical students and the training of doctors and nurses in the operating room …”
Section: Discussionmentioning
confidence: 99%
“…Studies also showed that the 3D endoscopy may be beneficial in the education of medical students and the training of doctors and nurses in the operating room. 19…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic surgery does, however, limit depth perception due to its 2D nature and as a result can lead to inaccuracies and lack of precision in surgery. Use of endoscopic surgery for pituitary resection also relies on the quality of cameras and monitors present in the department …”
Section: Discussionmentioning
confidence: 99%
“…Use of endoscopic surgery for pituitary resection also relies on the quality of cameras and monitors present in the department. 10 The electromagnetic navigation system was first introduced in 1988 by Sclondorff. It allows surgeons to operate with greater precision particularly when approaching the frontal sinus.…”
Section: Discussionmentioning
confidence: 99%